Information Security Assessment Process - Sultanov Kamoliddin Muxiddin o’g’li; Beknazarova Saida Safibullaevna (Periodica Journal, 2022)
The IB assessment model defines the scope of assessment reflecting the context of the IB assessment within the IB assessment criterion, the mapping and transformation of the assessment into the parameters of the assessment object, and also establishes indicators that ensure the IB assessment in the field of assessment.
Keywords: Information security; assessment process; business largely